A cost-effective method for tranquility mapping using open environmental data. (March 2020) - Pafi, Maria; Chalkias, Christos; Stathakis, Demetris
In this study, we propose a cost-effective method for tranquillity mapping using multi-criteria analysis and open geospatial data. We apply this method in an extended zone around a major Greek highway trespassing areas of high natural value. Composite criteria are developed through analytic functions and geostatistical methods to reflect either barriers or enablers of tranquillity. The results indicate that it is possible to identify tranquility zones which are spatially plausible. To verify the validity of the results, we calculate the Kappa coefficient (0.71) and the overall accuracy (80%) using preference data obtained from non-specialized photo-interpreters in a sample of places on Google Earth. We believe that this method can inform planning, especially in countries with a weak landscape policy.